The part that social media plays in advertising MSMEs goods in Patas 1 Village, Gunung Bintang Awi District, South Barito Regency - Marlina, Dika; Yuriawati, Ardita; Subakti, Akbar Ridho; Darmawan, Cahyo Wahyu (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This study discusses the role of social media in marketing products of Micro, Small, and Medium Enterprises (MSMEs) in Patas 1 Village, Gunung Bintang Awai District, South Barito Regency. MSMEs are an essential sector in the village's economy, with various businesses such as culinary, handicrafts, and traditional weapon production. Social media platforms like Facebook and WhatsApp have helped some MSME actors expand their markets and increase product sales. However, some MSMEs have yet to utilize social media due to limited knowledge fully. This study aims to evaluate the effectiveness of social media use in MSME marketing and provide appropriate strategy recommendations. The evaluation methods used were interviews and direct observation. The study's findings indicate that social media significantly expands market networks, builds consumer interactions, and increases product sales. However, challenges such as lack of creativity and competition from similar products remain. Therefore, training and socialization on social media use for MSME actors are necessary to maximize their marketing potential in the digital era